ANALISIS TINDAK TUTUR ILOKUSI DALAM PROSES PEMBELAJARAN GURU DAN SISWA KELAS III ARAFAH SDIT DAMBAAN UMMAT KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - Halid, Elan; Juniati , Nur Aizah (IdeBahasa, 2024)
The aim of this research is to describe the illocutionary speech acts in the learning process of teachers and students from Grade III Arafah at Integrated Islamic Elementary School (SDIT) Dambaan Ummat. The data sources are teachers and students’ conversations. The theory used is speech acts and illocutionary speech acts. Speech acts are part of the study of pragmatics. Pragmatics is a branch of linguistics that studies how context influences meaning in communication. Speech acts serve psychological and social functions beyond the discourse; they are actions conveyed through speech. Illocutionary acts include representative, directive, expressive, commissive, and declarative speech acts. Data collection method includes observation with video recording, interviews, documentation and transcription techniques. Technique of data analysis is noting and identifying the spontaneous utterances through video recording. The research results found 131 data: 24 instances of representative illocutionary acts, 66 instances of directive illocutionary acts, 20 instances of expressive illocutionary acts, 15 instances of commissive illocutionary acts, and six instances of declarative illocutionary acts.